Abundance of snow leopard (Panthera uncia) and its wild prey in Chhekampar VDC, Manaslu Conservation Area, Nepal - Devkota, B. P.; Silwal, T.; Shrestha, B. P.; Sapkota, A. P.; Lakhey, S. P.; Yadav, V. K. (Banko Janakari, 2017)
Snow leopard (Panthera uncia) is the striking symbol as well as an indicator of intact eco-regions of high mountains it inhabits. Despite the advancement in new methods, scholars argue that signs are still a reliable indicator for the purpose of habitat use study of snow leopards. The relative abundance of snow leopard and its major prey species such as blue sheep (Pseudois nayar) and Himalayan tahr (Hemitragus jemlahicus) in the Chhekampar Village Development Committee within the Tsum Valley of the Manaslu Conservation Area was determined by sign survey using Snow Leopard Information Management System (SLIMS) and block survey using Vantage Point Method, respectively. We also assessed human snow leopard conflict through household and key informant survey. The encounter rate of snow leopard signs were 3.57/km on an average, indicating low abundance, whereas prey species such as blue sheep and Himalayan tahr had 3.8 and 1.8 animals/km2, respectively. The livestock depredation rate was 1.29% with snow leopard accounting to only 0.32% of the total. Due to the low abundance of snow leopard but sufficient number of large-sized wild prey species, livestock predation by snow leopard was minimum, and therefore, the local people had positive perception towards snow leopard conservation. Though the present situation including the local religious tradition and social norms is supportive in conservation of snow leopard, it may not sustain unless incentive programs are encouraged timely. Banko Janakari, Vol. 27, No. 1, Page : 11-20